The Prevalence of Stress Urinary Incontinence in Coastal Community from Riau Province - Edy Fakhrizal; Ruza Prima Rustam; Sri Wahyu Maryuni (Future Science, 2022)
Stress Urinary Incontinence (SUI) significantly affects women’s quality of life through physical and psychosocial limitations and sexual dysfunction. This condition may cause a huge individual and family burden, leading to a global burden. The coastal area is geographically located in islands confined by the sea, thus becoming the basis of health problems due to its limited access to healthcare facilities. No study has been conducted to identify the SUI prevalence rate. This study aims to help determine problems caused by SUI, eventually conceiving effective prevention and treatment strategies to be proposed to health policymakers. This research is a quantitative study with women of reproductive age (20 – 44 years old) and >44 years old in 4 coastal areas (Bengkalis, Dumai, Siak, and Rumbai Pesisir) as the key population. Of 320 patients, 178 (53,80%) were screened for urinary incontinence. Among 178 screened subjects, 152 (85%) were classified as stress urinary incontinence, with the highest incidence rate found at Dumai, with 59 (39%) cases. Bengkalis, Siak, and Pekanbaru had an incidence rate of 51 (33%), 33 (22%), and 9 (6%), consequently. This study found most women had urinary incontinence, with the most common type being stress urinary incontinence. Based on this study, due to the high prevalence of SUI, the authors agreed that effective prevention and treatment strategies are needed to prevent SUI's severity and further development.